2010
DOI: 10.1099/mic.0.035154-0
|View full text |Cite
|
Sign up to set email alerts
|

PAP1 [poly(A) polymerase 1] homozygosity and hyperadenylation are major determinants of increased mRNA stability of CDR1 in azole-resistant clinical isolates of Candida albicans

Abstract: Using genetically matched azole-susceptible (AS) and azole-resistant (AR) clinical isolates ofCandida albicans, we recently demonstrated that CDR1 overexpression in AR isolates is due to its enhanced transcriptional activation and mRNA stability. This study examines the molecular mechanisms underlying enhanced CDR1 mRNA stability in AR isolates. Mapping of the 39 untranslated region (39 UTR) of CDR1 revealed that it was rich in adenylate/uridylate (AU) elements, possessed heterogeneous polyadenylation sites, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…In another study, it was found that poly(A) polymerase homozygosity and hyperadenylation are responsible for the increased stability of CDR1 mRNA (71). However, the half-life of Cdr1p did not change between AS and AR isolates, thus ruling out any possible role for Cdr1 protein stability in drug resistance (70).…”
Section: Regulation Of Cdr1 Transcriptionmentioning
confidence: 99%
“…In another study, it was found that poly(A) polymerase homozygosity and hyperadenylation are responsible for the increased stability of CDR1 mRNA (71). However, the half-life of Cdr1p did not change between AS and AR isolates, thus ruling out any possible role for Cdr1 protein stability in drug resistance (70).…”
Section: Regulation Of Cdr1 Transcriptionmentioning
confidence: 99%
“…For example, LOH appears to play an important role in acquired azole resistance in C. albicans: homozygosis of the hyperactive alleles of ERG11, TAC1, or MRR1 (which encode the target of azole drugs and transcription factors that upregulate drug efflux pumps) is associated with increased azole resistance (39,50,204). Homozygosis of the PAP1 allele within the MTL locus also confers different levels of resistance to drugs (88,121). Similarly, resistance to the antifungal 5-flucytosine (5-FC) was associated with homozygosis of a hyperactive FUR1 allele (45).…”
mentioning
confidence: 99%
“…to antifungal drugs is related to their prolonged use. Among the mechanisms that contribute to this phenomenon are the overexpression or mutation of genes, such as ERG11, CDR1, CDR2 and MDR1 that encode efflux pumps (Sanglard et al, 2003;Basso Junior et al, 2010;Manoharlal et al, 2010), as well as the ERG-3 gene encoding the enzyme ∆ 5.6 sterol dessaturase, important in the synthesis of ergosterol (Sanglard et al, 2003) and alterations in the lipid composition of the fungal plasma membrane, which hinders the influx of the drug into the cell (Loffler et al, 2000). It should be pointed out that these mechanisms can occur simultaneously, contributing to increase the phenomenon of resistance.…”
Section: Introductionmentioning
confidence: 99%